Pharmaco-Therapeutic Study Of Tankadi Yog (Kalpit Yog) In The Management Of Karshya W.S.R. To Malnutrition. - Chorotiya, Preeti; Dhakad, Anjana; Singh, Chandan; Adlakha, Manoj (International Research Journal of Ayurveda & Yoga, 2020)
When body unable to get the proper diet and healthy food stuff that condition of body is termed as Malnutrition. A malnourished person finds that their body has difficulty doing normal things such as growing and resisting disease. Physical work becomes problematic and even learning abilities can be diminished. For women, pregnancy becomes risky and they cannot be sure of producing nourishing breast milk. In some cases, malnutrition is very mild and causes no symptoms. However, sometimes it can be so severe that the damage done to the body is permanent, even though you survive. Malnutrition continues to be significant problem all over the world, especially among children. Poverty, natural disasters, political problems, and war all contribute to conditions even epidemics of malnutrition and starvation, and not just in developing countries. Malnutrition also causes due to weak immunity. Main aim of the study is evaluate the efficacy of “Tankadi Yog” as internal medicine in the management of Karshya. It is randomized control clinical trial. The study was conducted on 40 clinically diagnosed Patients of Karshya. They are randomly allocated into two groups after screening. Group-A(Tankadi Yog), Group-B(Manoll Syrup as a standard drug). Observation & result assessed on the basis of difference in the score of sign and symptoms. All the details regarding the study are further detailed. There are many drugs mention in classical books of ayurveda for Karshya. One of them is Tankadi Yoga.